STRATEGI KOMUNIKASI PEMASARAN PARIWISATA SATWA DALAM MENGHADAPI COVID-19 SECARA DIGITAL DI TAMAN SAFARI BOGOR - Garda Carumna Iskayunoka; Pitoyo Pitoyo (Interaksi: Jurnal Ilmu Komunikasi, 2023)
This study aims to identify and analyze the communication and marketing strategies of zoo tourism conducted by Taman Safari Bogor as an effort to deal with the Covid19 pandemic. To obtain data, we make observation, interview and documentation. An interviewee in this case is the Section Chief Public Relations of Taman Safari Bogor. This type of study is qualitative using descriptive analysis and the paradigm used is constructivism. The results of this study, Taman Safari Bogor in dealing with the Covid-19 pandemic by implementing several strategies, including 5-step communication planning and marketing in the tourism sector. Noted that Covid-19 has made Taman Safari Bogor face two conditions, namely when it is closed and can operate by following government regulations, thus impacting revenue from visitors for this reason, planning is needed to deal with the impact of Covid-19 by creating a campaign to help maintain animals targeted at all elements of society and convince visitors that Taman Safari Bogor sterile so they can be visited. Taman Safari Bogor conducts marketing through social media and websites by conducting a Virtual Tour at an adjusted price and cooperation with various commercial media and TV shows to convey information about Taman Safari Bogor.